Special Programme for Research and Training in Tropical Diseases-coordinated Multicountry Study to Determine the Burden and Causes of Residual Malaria Across Different Regions. (27th April 2021) - Fouque, Florence; Knox, Tessa
Abstract: The burden and causes of residual malaria were investigated between 2015 and 2019 through 5 research projects coordinated by the Special Program for Research and Training in Tropical Diseases (TDR), cosponsored by the United Nations Development Programme, UNICEF, the World Bank, the World Health Organization (WHO) and the WHO Global Malaria Programme. The 5 projects included 10 countries in 4 WHO regions: Africa, the Americas, South-East Asia, and the Western Pacific. The countries represented a range of malaria endemicities, from low to high levels of transmission. The main findings of the projects indicate that overall the core malaria vector control tools (long-lasting insecticidal nets [LLIN] and indoor residual spraying) were not deployed in the optimal way and/or not efficient in many settings of the supported projects. Furthermore, vector biting behavior and human activity–associated factors strongly contributed to malaria persistence. Changes in vector species composition and abundance, with an increase in outdoor biting, were also reported. Some of these factors may be an adaptation of the vectors to the deployment of the tools and/or can be linked to other sectors, such as agricultural practices, environmental changes, social factors, and water management. Human behaviors and sleeping habits that included activities and sleeping outside villages in unprotected dwellings were another part of the problem. The evidence collated demonstrates the need for new approaches, such as the multisectoral one and new vector control tools, all adapted to the local contexts and integrated into current malaria programs.